Quantitation of DEFA1A3 gene copy number polymorphism by allele specific amplification and real-time PCR - Németh, Balázs Csaba (Acta Biologica Szegediensis, 2013)
Some of the PCR based genotyping methods are faster and less expensive than sequencing in population-wide studies. One of the cost effective solutions is the allele specific amplification (ASA). We applied this method for quantitative analysis of defensin A1 (DEFA1) and defensin A3 (DEFA3) genes which are known to have copy number polymorphism in the human genome. The proteins encoded by these genes are human alpha defensins / human neutrophil peptides 1 and 3. Their antimicrobial mechanisms have an important role in the function of innate immune system. Our aim was to improve the reproducibility of ASA using 14 different mastermixes (MMX). Unfortunately, not all MMX-s are suitable for ASA investigations due to their different characteristics of polymerase activity. Here we investigated 14 commercial MMX-s whether they are capable for ASA test.